Association of environmental exposure to chromium with differential DNA methylation: An epigenome-wide study - Zhao, Meiduo; Wu, Jingtao; Xu, Jing; Li, Ang; Mei, Yayuan; Ge, Xiaoyu; Yin, Guohuan; Liu, Xiaolin; Wei, Lanping; Xu, Qun (Frontiers in Genetics, 2023)
Previous studies have reported that chromium (Cr)-induced epigenetic alterations and DNA methylation play a vital role in the pathogenesis of diseases induced by chromium exposure. Epigenomic analyses have been limited and mainly focused on occupational chromium exposure; their findings are not generalizable to populations with environmental Cr exposure. We identified the differential methylation of genes and regions to elucidate the mechanisms of toxicity related to environmental chromium exposure. DNA methylation was measured in blood samples collected from individuals in Cr-contaminated (n = 10) and unexposed areas (n = 10) by using the Illumina Infinium HumanMethylation850K array. To evaluate the relationship between chromium levels in urine and CpG methylation at 850 thousand sites, we investigated differentially methylated positions (DMPs) and differentially methylated regions (DMRs) by using linear models and DMRcate method, respectively. The model was adjusted for biologically relevant variables and estimated cell-type compositions. At the epigenome-wide level, we identiﬁed five CpGs [cg20690919 (pFDR =0.006), cg00704664 (pFDR =0.024), cg10809143 (pFDR =0.043), cg27057652 (pFDR =0.047), cg05390480 (pFDR =0.024)] and one DMR (chr17: 19,648,718-19,648,972), annotated to ALDH3A1 genes (p < 0.05) as being significantly associated with log2 transformed urinary chromium levels. We observed the signiﬁcant enrichment of genes involved in DNA repair and cell proliferation, which can lead to the accumulation of DNA damage, genomic instability, and carcinogenesis. Environmental chromium exposure is associated with DNA methylation, and the significant DMPs and DMR being annotated to cause DNA damage and genomic instability were found in this work. Research involving larger samples is required to further explore the epigenetic effect of environmental chromium exposure on health outcomes through DNA methylation.